IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI KAB. OGAN KOMERING ULU - Nurlailah Nurlailah (JURNAL DINAMIKA, 2021)
To reduce the number of Covid-19 cases, in addition to carrying out health protocols, it is necessary to carry out special protective measures, namely vaccination. The purpose of this study is to describe the implementation of the COVID-19 vaccination policy in Ogan Komering Ulu Regency, with a theoretical approach Implementation policy of George C. Edward III viewed from 4 aspects. 1) Communication: Communication in the implementation of the Covid-19 vaccination policy in Ogan Komering Ulu Regency has gone well, both in terms of transmission and clarity. But there are inconsistencies in the requirements for vaccine recipients, which can confuse the public. 2) Resources: Human resources, budgetary resources, equipment resources and authority resources, although the numbers are still lacking, they are adequate and have good performance. 3) Disposition: The implementer of the Covid-19 vaccination policy who is highly dedicated and has skill standards has been selectively selected in the implementation of the vaccination policy in Kab. OKU. However, the provision of incentives is not balanced with the number of personnel implementing vaccinations in the field. 4) Bureaucratic Structure: the vaccination policy in OKU District uses the bureaucratic structure of OKU District Health Office. In its implementation, it already has an SOP, and with a wide area coverage, more intensive coordination is needed, so that the Covid-19 vaccination policy in Kab. OKU can be implemented properly.